2022
DOI: 10.1111/jfb.15019
|View full text |Cite
|
Sign up to set email alerts
|

Mercuric chloride‐induced oxidative stress, genotoxicity, haematological changes and histopathological alterations in fish Channa punctatus (Bloch, 1793)

Abstract: The present study was undertaken to investigate the adverse effects of mercuric chloride (HgCl2) overload in the fish Channa punctatus. Two sublethal test concentrations of HgCl2 (1/20th and 1/10th of 96 h LC50 i.e., 0.03 mg l−1 (low concentration) and 0.07 mg l−1 (high concentration), respectively, were used for exposure. Blood, liver and kidney tissues of the control and exposed specimens were sampled at intervals of 15, 30, and 45 days to assess alterations in oxidative stress, genotoxicity haematological p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 101 publications
1
17
0
Order By: Relevance
“…In this study mercuric chloride can induce oxidative stress mediated DNA strand breaks which causes genotoxicity in fish Channa punctata . Similarly, Trivedi et al, 2022 2 have reported that mercuric chloride can cause genotoxicity in targeted fish. The resulting oxidative damage disrupts cellular functions, initiating lipid peroxidation in biomolecules like lipids and proteins.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study mercuric chloride can induce oxidative stress mediated DNA strand breaks which causes genotoxicity in fish Channa punctata . Similarly, Trivedi et al, 2022 2 have reported that mercuric chloride can cause genotoxicity in targeted fish. The resulting oxidative damage disrupts cellular functions, initiating lipid peroxidation in biomolecules like lipids and proteins.…”
Section: Resultsmentioning
confidence: 95%
“…A fluorescent dye 2′, 7′-dichlorodihydrofluorescein (20 µM, DCFH-DA; Sigma Aldrich, USA) was used to quantify ROS level in the blood of test fish 2 , 28 . The fluorescence intensity of stained blood cells depicts the amount of ROS generated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of adaptation to contaminants is thus crucial for adequate environmental risk assessment. Many studies on experimental as well as wild populations have improved our understanding of how mercuric toxicity disrupts metabolic, endocrine and cellular pathways, and have provided a basis for the development of biomarkers for mercury pollution (Driscoll et al, 2013, Branco et al, 2017, Vasconcellos et al, 2021, Olsvik et al, 2021, Trivedi et al, 2022). In contrast, relatively few studies have investigated how genetic adaptation shapes the biological responses to mercury pollution and, therefore, how populations under pollution stress ultimately manage to persist (Belfiore and Anderson, 2001, Budnik and Casteleyn, 2019, Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although MeHg is the most toxic form [ 12 ], HgCl 2 is the most common and harmful form since it can pass across biological membranes and interact with amino acids forming organo-mercury complexes [ 13 ]. The reported Hg 2+ toxicity for fish is in the form of brain oxidative stress, inhibition of hepatic biotransformation enzymes, genotoxicity in blood, and reproductive alterations [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%